Penerapan Spiral Method untuk Pengembangan Sistem Pencegahan Pemalsuan Sertifikat dengan Penerapan Tanda Tangan Digital dan Verifikasi Online - Zulkarnaim, Nuralamsah; Mansyur, Muh. Fuad (Program Studi Teknik Informatika Universitas Pamulang, 2024)
A certificate is a legal document that proves that someone has passed a certification exam or has taken part in certain activities. Certificates are generally issued by authorized institutions as legal evidence or recognition. However, there are several cases where certificates that should be issued by official institutions are falsified by parties who want to take advantage. This is the basis for this research to be carried out with the aim that certificates issued by the Faculty of Engineering, University of West Sulawesi can be prevented from being faked by implementing a digital signature in the form of a QRCode whose authenticity can be traced through online verification. To develop this system, this research applies the spiral method. The spiral method was chosen as a development model by considering the flexibility it offers for further development according to needs. The results of this research produce a system that can produce certificates whose validity can be traced through online verification either by searching the certificate number or using QRCode scanning. In this way, prevention of counterfeiting of certificates issued by the Faculty of Engineering, Unsulbar can be minimized.